Knowledge, attitude and practice of children and young adults on road traffic injuries - Mahfozphour, Soad; Soori, Hamid; Einy, Elaheh; Iranfar, Manigheh; Amiri, Zohreh; Hadadi, Mashyaneh; Hydar, Farhad (Advances in Nursing & Midwifery, 2011)
Knowledge, attitude and practice of children and young adults on road traffic injuries Mahfozphour, S.1 (PhD); Soori, H.2* (PhD); Einy, E.3 (MS); Iranfar, M.4 (MS), Amiri, Z.5 (PhD); Hadadi, M.6 (PhD); Hydar, F.7 (BS) 1. Assistant Professor, Faculty of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 2. Professor, Faculty of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 3. Lecturer, Dept of Midwifery, Research Center for Safety Promotion and Injury Prevention, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 4. Researcher, Research Center for Safety Promotion and Injury Prevention, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 5. Associate Professor, Faculty of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 6. Supervisor, Center for Accident Prevention and Safety Promotion in Center for Accident and Emergency Management of The Ministry of Health, Tehran, Iran. 7. Expert and Police Officer, Applied Research Office of Traffic Police, Shahrak Azmayesh, Tehran, Iran. Abstract Background and aim According to records, the rate of road traffic injuries among children and adolescents is high. The aim of this study was to determine knowledge, attitude and practice of children, adolescents and young adults between 9 and 30 regarding traffic accidents in 2008. Materials and methods In this descriptive study, 304 children and adolescents between 9 and 14 as well as 327 young adults between 15 and 30 were randomly selected according to their distribution in 19 educational districts and all universities of Tehran in 2008. Data were collected by a 3-part questionnaire validated and made reliable by content and test-retest methods respectively after taking the informed consent of the subjects. The scores were divided in 3 ranks: Good (above 75%), moderate (50%-75%), and poor (below 50%). Findings Means of age in the first and second groups were 11.7±1.6 and 20.7±4.3 respectively. Overall, 50.7% was male. The practice score of females in the first group (9-14 years old) was better than males (P<0.001) and, among males in the second group (15-30 years old), attitude as well as practice scores were higher than females (P<0.02). Attitude scores in high school students were better than primary school students (P<0.043). In university students, attitude and practice scores were higher than others (P<0.001). Knowledge and practice scores were higher in police assistants at primary schools than high schools (P<0.003). Conclusion The findings revealed the need of both groups for more educational programs regarding traffic accidents and injuries. Keywords: Knowledge, Attitude, Practice, Traffic accidents, Children, Young adults. *Corresponding Author: Hamid Soori. Professor, Faculty of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: hsoori@Yahoo.com